2014
DOI: 10.1155/2014/829894
|View full text |Cite
|
Sign up to set email alerts
|

Piper nigrumLeaf and Stem Assisted Green Synthesis of Silver Nanoparticles and Evaluation of Its Antibacterial Activity Against Agricultural Plant Pathogens

Abstract: Utilization of biological materials in synthesis of nanoparticles is one of the hottest topics in modern nanoscience and nanotechnology. In the present investigation, the silver nanoparticles were synthesized by using the leaf and stem extract of Piper nigrum. The synthesized nanoparticle was characterized by UV-vis spectroscopy, X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), energy dispersive X-ray analysis (EDAX), and Fourier Transform Infrared Spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(101 citation statements)
references
References 29 publications
4
82
0
2
Order By: Relevance
“…With 50 ppm and 100 ppm by 84.56% and 93.5% respectively. Paulkumar et al [33] found that the silver nanoparticles have excellent antimicrobial activity against plant pathogens Citrobacter freundii and Erwinia cacticida, they concluded that the silver nanoparticles have a beneficial application in field of plant disease control. Kim et al [34] studied the antimicrobial activity of silver nanoparticles against Acidovorax citrulli and they found the growth of five strains of A. citrulli was inhibited by AgNPs.…”
Section: Effect Of Chitosan and Silver Nps On Radial Growth Of B Fabmentioning
confidence: 99%
“…With 50 ppm and 100 ppm by 84.56% and 93.5% respectively. Paulkumar et al [33] found that the silver nanoparticles have excellent antimicrobial activity against plant pathogens Citrobacter freundii and Erwinia cacticida, they concluded that the silver nanoparticles have a beneficial application in field of plant disease control. Kim et al [34] studied the antimicrobial activity of silver nanoparticles against Acidovorax citrulli and they found the growth of five strains of A. citrulli was inhibited by AgNPs.…”
Section: Effect Of Chitosan and Silver Nps On Radial Growth Of B Fabmentioning
confidence: 99%
“…Recently, sunlight-induced rapid synthesis of silver nanoparticles has been reported by our group [18,19]. Biosynthesis of silver nanoparticles using bark of Cinnamon zeylanicum [20], Piper nigrum [21], Breynia rhamnoides [22], Avicennia marina [23], Callicarpa maingayi [24], Cissus quadrangularis [25], Artocarpus elasticus [26], and Saraca indica [27] has also been reported. The use of plant barks for the synthesis of nanoparticles avoids the problems that arise due to seasonal variation of biochemicals in the leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported spherical silver nanoparticles with size ranging 5-40 nm which reported to have significant activity against normal (LBA4404) and multidrug resistant (LBA4404 MDR) Agrobacterium tumefaciens. Similarly, silver nanoparticles synthesized from Piper nigrum leaf and stem extracts exhibited antibacterial activity against phytopathogenic bacteria such as Citrobacter freundii and Erwinia cacticida (Paulkumar et al, 2014). Further, the antibacterial activity of phytosynthesized silver nanoparticles using aqueous extract of Helianthus tuberosus (sunroot tuber) against phyto pathogenic bacteria was studied by Aravinthan et al (2015).…”
Section: Nanoagroparticles As Potential Nanobactericidesmentioning
confidence: 99%